Discussion of Medicine and Religion: Study of Missionary Hospitals in Modern Shanghai, China - Lyu-Hua Chen; Li-Yun Chen; Er-Liang Wang (Chinese Medicine and Culture)
Abstract. In modern times, 15 missionary hospitals were established in Shanghai, including 6 Protestant hospitals and 9 Catholic hospitals. These hospitals were the products of Western missionaries in China. The establishment of missionary hospitals objectively introduced Western medicine into China and changed its original medical system. Based on documents and periodicals, Shanghai archives, Xujiahui library materials, hospital historical records, and domestic and foreign library historical materials, this paper systematically reviews the development of missionary hospitals in Shanghai, and discusses their balance between medicine and religion, to provide ideas and references for future research.